Appeals to the Hispanic Demographic: Targeting through Facebook Autoplay Videos by the Clinton Campaign during the 2015/2016 Presidential Primaries. Issue 3 (2nd October 2017) - Elder, Edward; Phillips, Justin B.
Abstract : By looking at the autoplay videos posted and shared on Hillary Clinton's Facebook account during the2015 /2016 primary election season, this article offers much needed insight into the communication aspect of campaign targeting. Using data analysis extracted from the leading social media platform, the article examines what groups of Hispanic Facebook users were attracted to Clinton's targeted autoplay videos, what elements within these videos best enticed these people into liking the videos, and if the Clinton campaign appeared to learn what types of autoplay videos were most effective over the course of the primary season.